HUBUNGAN ANTARA FLAGGING ATYPDEP DI ALAT CELL-DYN 3200 DAN KEBERADAAN PLASMODIUM Spp DI DALAM DARAH PENDERITA DI RSUD DR.SOETOMO SURABAYA - Esti Rohani; J Nugraha (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2011)
Malaria is a parasitic disease worldwide with a high morbidity and mortality. A rapid and accurate methods is needed to detectthe presence of malaria parasites in blood. A flagging system atypical depolarization (atypdep) on CBC result from Cell-Dyn 3200instrument has been related with malaria infection. An observational cross sectional approach with a total of 48 samples were obtainedfrom inpatients in the Dr. Soetomo Hospital Surabaya. Samples were screened with Cell-Dyn 3200 analyzer for CBC found atypdepflagging. The positive samples were later confirmed by microscopic to detect malaria parasites. From 48 samples with atypdep flagging,seven samples were positive of malaria in peripheral blood smear (13.1%). Most frequent atypdep flagging was seen in malignant disease(18.7), an approximately 54.6% of the sample is not accompanied by symptoms of fever. Lekositosis and anemia were found in each of20 samples (41.6%) and thrombocytopenia in 33.3% of the samples. The presence of atypdep flagging does not necessarily indicate theexistence of malaria infection or it could be said that atypdep flagging is not always associated with the presence of malaria infection.The usage of an atypdep flagging on Cell-Dyn instrument in non-endemic areas such as Surabaya is just an alert sign to evaluate themalaria infection rather than a screening method to detect malaria.